Modelling the trajectory of the corpses of mountaineers who disappeared in 1926 on Aletschgletscher, Switzerland - Jouvet, Guillaume; Funk, Martin (Journal of Glaciology, 2014)
ISSN:0022-1430 ISSN:1727-5652